Woollys walk: usborne touchy feely farmyard tales - Cartwright, Stephen (Usborne London, 2009)
"Woolly's Walk" is a charming children's book that follows Woolly, a friendly sheep, on an adventurous stroll through the countryside. As Woolly walks, he encounters various animals and discovers the beauty of nature around him. The story emphasizes themes of curiosity, friendship, and exploration, inviting young readers to appreciate the wonders of the world. With delightful illustrations and a gentle narrative, the book encourages children to engage with their environment and fosters a sense of adventure in everyday activities.